High prevalence of dysfunctional, asymmetrical, and painful movement in elite junior Australian Football players assessed using the functional movement screen - Fuller, J. T.; Chalmers, S.; Debenedictis, T. A.; Townsley, S.; Lynagh, M.; Gleeson, C.; Zacharia, A.; Thomson, S.; Magarey, M. (Journal of Science and Medicine in Sport, 2017)
Objectives: The purpose of this study was to describe the prevalence of dysfunctional, asymmetrical, and painful movement in junior Australian Football players using the Functional Movement Screen (FMS). Design: Cross-sectional study. Methods: Elite junior male Australian Football players (n = 301) aged 15-18 years completed pre-season FMS testing. The FMS consists of 7 sub-tests: deep squat, hurdle step, in-line lunge, shoulder mobility, active straight leg raise, trunk stability push-up (TSPU) and rotary stability. The shoulder mobility, TSPU, and rotary stability tests were combined with an accompanying clearing test to assess pain. Each sub-test was scored on an ordinal scale from 0 to 3 and summed to give a composite score out of 21. Composite scores =14 were operationally defined as indicating dysfunctional movement. Players scoring differently on left and right sides were considered asymmetrical. Players reported whether they missed any games due to injury in the preceding 22 game season. Results: Sixty percent of players (n = 182) had composite scores =14, 65% of players (n = 196) had at least one asymmetrical sub-test, and 38% of players (n = 113) had at least one painful sub-test. Forty-two percent of players (n = 126) missed at least one game in the previous season due to injury. Previous injury did not influence composite score (p = 0.951) or asymmetry (p = 0.629). Players reporting an injury during the previous season were more likely to experience pain during FMS testing (odds ratio 1.97, 95% confidence interval 1.23-3.18; p = 0.005). Conclusions: Junior Australian Football players demonstrate a high prevalence of dysfunctional, asymmetrical, and painful movement during FMS testing. AUTORREFERAT